2019
DOI: 10.1038/s41598-019-43353-w
|View full text |Cite
|
Sign up to set email alerts
|

Climate drivers of hospitalizations for mycoses in Brazil

Abstract: Climate can modulate human health at large spatial scales, but the influence of global, regional, and local environments remains poorly understood, especially for neglected diseases, such as mycoses. In this work, we present the correlation between climatic variables and hospitalizations for mycoses in Brazilian state capitals, evaluating the period of 2008 to 2016 at different time scales. The results indicate that climate modulates the hospitalizations for mycoses differently at annual and monthly time scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…In this study, we observed that hospitalisations for mycoses have a seasonal cycle accompanied by climate variables, such as precipitation and maximum and minimum temperature . In addition to socio‐economic susceptibility, the seasonality of hospitalisations for mycoses was also found to represent an indicator of environmental vulnerability.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…In this study, we observed that hospitalisations for mycoses have a seasonal cycle accompanied by climate variables, such as precipitation and maximum and minimum temperature . In addition to socio‐economic susceptibility, the seasonality of hospitalisations for mycoses was also found to represent an indicator of environmental vulnerability.…”
Section: Discussionmentioning
confidence: 84%
“…In addition to socio‐economic susceptibility, the seasonality of hospitalisations for mycoses was also found to represent an indicator of environmental vulnerability. In addition, the minimum temperature, influenced by La Niña, was the key climatic variable in periods with high prevalence of HM …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the clinical importance of fungal infections caused by theses pathogenic yeasts, interestingly, climatic abnormalities due to phenomena such as La Niña and El Niño have recently been described as important in the distribution and occurrence of mycoses in countries influenced by them [59].…”
Section: Pathogenic Yeast Infections: a Serious Health Problemmentioning
confidence: 99%